In vitro evaluation of sodium butyrate on the growth of three Salmonella serovars derived from pigs at a mild acidic pH value - Hollmann, Isabell; Lingens, Jan Berend; Chuppava, Bussarakam; Wilke, Volker; Abd El-Wahab, Amr; Buch, Juhle; Hankel, Julia; Ahmed, Marwa F. E.; Visscher, Christian (Frontiers in Veterinary Science, 2022)
Foodborne zoonotic diseases can be transferred into the food chain at the stage of livestock farming. As an emerging public health challenge, practicable reduction measures in porcine health management for Salmonella are constantly being investigated. This in vitro study aimed to determine the influence of six different sodium butyrate (SB) concentrations (0, 5, 10, 20, 40, and 80 mM) on the growth of three different Salmonella (S.) enterica serovars at a constant pH value of 6.0, corresponding to conditions in the pig’s hindgut. S. Derby and S. Typhimurium, isolated from a pig farm and S. Typhimurium DSM 19587, which served as control, were used. Broth microdilution assay was applied to record Salmonella growth in the presence of different SB-concentrations over six different incubation periods (0, 1, 2, 4, 6, and 24 h). Results were quantified in the log colony-forming units (log10 CFU/mL). For 1 h incubation, the addition of SB showed no significant differences in the range of initial Salmonella dose of about 5.7 log10 between concentrations (0 – 80 mM, 5.26±0.10 – 5.60±0.07 log10, p > 0.05). After 6 h, for SB addition the range of Salmonella counts was significantly lower compared to no addition of SB (5 – 80 mM, p < 0.05), 6.78±0.84 – 7.90±0.10 log10 for 5 mM and 7.53±0.04 – 8.71±0.22 log10 for 0 mM. Moreover, for SB concentrations of 40 and 80 mM no difference in the range of Salmonella counts over 6 h were obtained (5.23±0.11 – 5.38±0.05 log10, p > 0.05) and minor Salmonella growth was recorded at the earliest after 24 h incubation. Growth rates for varying SB concentrations and incubation times were confirmed in a similar manner for the three serovars. Obtained results suggest that increasing SB concentrations suppress Salmonella growth, for concentrations of 5 – 20 mM over a 6 h incubation period and for 40 and 80 mM over a 24 h incubation period. When transferring these in vitro findings to the porcine organism it may be assumed that Salmonella reduction can be achieved by increased butyrate content in the chyme of the large intestine.